Fucoidan Hydrogels Significantly Alleviate Oxidative Stress and Enhance the Endocrine Function of Encapsulated Beta Cells. (10th June 2021) - Reys, Lara L.; Vaithilingam, Vijayaganapathy; Sthijns, Mireille M. J. P. E.; Soares, Eduardo; Rademakers, Timo; de Vries, Rick; Mohammed, Sami G.; de Bont, Denise; Jetten, Marlon J.; Hermanns, Carolin; Filho, Omar Paulino da Silva; Stell, Adam; et al.
Abstract: Microencapsulating pancreatic islets in immunoprotective alginate hydrogels is a promising strategy for treatment of type 1 diabetes. However, this strategy is limited by inflammation and hypoxia mediated oxidative stress, due to encapsulation and the hydrogel itself, leading to impaired insulin secretion and limited short and long term cell survival. Herein, the antioxidant effect of fucoidan, an algae derived polysaccharide, on beta cells, and its positive effects on encapsulated beta cell viability and function is presented. Fucoidan from Fucus vesiculosus (FF) exhibits a high total antioxidant capacity, and free radical scavenging activity, and is able to significantly alleviate intracellular oxidative stress in rat insolinoma beta cells (INS1E). In addition, FF significantly increases insulin secretion in a dose‐ and time‐dependent manner. When FF is incorporated in ultrapure alginate used for microencapsulation of primary rat islets, both viability and glucose responsiveness of rat islets in these socalled Fucogel microcapsules (Fucocaps) are found to be significantly higher compared to islets encapsulated in alginate alone. Similar results are obtained with INS1E pseudoislets and neonatal pig islets. Fucocaps can provide a redox‐modulatory niche and an immune barrier for islets and beta cells in the same time leading to significantly improved survival and endocrine function by mitigating oxidative stress. Abstract : The present study is the first to explore the potential of fucoidan, marine sulfated polysaccharide, for pancreatic islet encapsulation. Fucoidan has high fucose contents with sulfate groups, demonstrating potent antioxidant properties significantly alleviating oxidative stress and enhancing the viability and function of encapsulated beta cells. The fucoidan‐based hydrogel is thus assessed as a biomaterial for bioengineered immunoprotective beta cell replacement systems.